Analysis of surface changes of burning nanopowders using digital processing of laser monitor images; Applied Optics; Vol. 59, iss. 18 - Gubarev F. A. Fedor Aleksandrovich; Kim S. Sergey; Li Lin; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich (2020, 2020)
Title screen